Prevalence of Gastrointestinal Symptoms in COVID-19 Patients; Result From Tertiary Care Hospital in Pakistan - Hinna, Rashk e; Usman Munir, Muhammad; Manzoor, Mohteshim; Ali, Irfan; Khan, Rao Saad Ali; Afzal, Muhammad (Scripta Medica, 2024)
Background/Aim: The most commonly reported COVID-19 symptoms are high-grade fever, cough and body aches with atypical symptoms ie vomiting, diarrhoea and abdominal discomfort. The primary purpose of this research was to ascertain the frequency of gastrointestinal problems experienced by patients due to COVID-19. Goal was to determine whether or not there was a correlation between the severity of COVID-19 disease and the presence of gastrointestinal symptoms in studied individuals.Methods: The study was conducted at the Gastroenterology Department, PEMH Rawalpindi, Pakistan from January 2022 to January 2023. Confirmed inpatient cases of COVID-19 disease were recruited, referred to Pak Emirates Military Hospital Rawalpindi, Pakistan. Real-time polymerase chain reaction (RT-PCR) verified the presence of COVID-19 in the patients of this research study. Results: There were 345 patients (335 men and 10 women), with 116 patients exhibiting gastrointestinal symptoms and only 27 patients presented with severe disease. Diarrhoea and anorexia were the most frequently reported digestive symptoms with a frequency of 44 (12.8 %) and 34 (9.9 %), respectively. Clinical outcomes and disease severity were not significantly different between patients with and without digestive issues. Conclusion: The course of a COVID-19 infection seems to include gastrointestinal symptoms, which include, but are not limited to vomiting, diarrhoea, anorexia, etc. Numerous gastrointestinal symptoms are linked to COVID-19 infection even in the absence of respiratory symptoms. As a result, COVID-19 infection should be taken into account for individuals who primarily present with gastrointestinal symptoms. The establishment of personalised COVID-19 therapies will be aided by an understanding of the varying susceptibility of the individual gastrointestinal system to SARS-CoV-2.